De Marx a Altieri: limites do balizamento jurídico para a produção agroecológica nos marcos do capitalismo - Rosa, Vanessa de Castro (2019)
Since the international environmental awareness process initiated in the 1960s, much progress has been made in the environmental legislative production - international and national - and very little in the effectiveness of environmental protection. However, the risks have increased with GMOs, nuclear energy and agrochemicals, as well as old problems, such as global warming and pollution of rivers and oceans, continue to rise. This scenario awakens attention to the treatment of the environmental and agrarian issue from the right, that is, within the normativist paradigm. In this way, based on the method of historical materialism, the environmental and agrarian question is analyzed in the capitalist mode of production, in order to verify the real possibility of a model of capitalist sustainable development. The study focuses on the ecological thinking of Karl Marx and his contribution to the development of agroecology as a way of repairing metabolic failure, as pointed out by Marx and John Bellamy Foster. From this analysis, the role of law, according to the proposal of Marx and Pachukanis, is investigated to evaluate the limits of the construction of an agroecological agrarian system, from the legal form and the political form. It can be seen that in the capitalist mode of production there is no possibility of building a green or sustainable capitalism, nor a State of Environmental Law, which also makes it impossible to implement agroecology as a substitute for agribusiness, stressing that incompatibility is not of agricultural techniques, but of the functioning structure of capital, of which law and state are subservient emanations. The limits to agroecology are defined in the logic of accumulation of capital, in the sphere of valorization of value and expansion of production and consumption. It remains to know, given the understanding of agroecology as a set of knowledge, science and social movement, the possibilities of building new forms of sociability, understanding and socio-political organization, as a way to try to overcome the current mode of production, because capitalism had its origin in the field and in it can arise the rupture